Nutrition and feeding of organic pigs [ - Blair, Robert , 1933- (CABI, 2007)
Organic animal production has increased rapidly in recent years to keep up with the increasing consumer demand for organic meats. There are many guidelines and restrictions on what go into the feedstuffs of organically farmed animals, from which difficuties arise when trying to ensure a well balanced nutritious diet without the use of any supplements. The first comprehensive text on feeding organic pigs, this book presents advice on formulating appropriate diets and integrating them into organic pig production systems. It outlines the international standards of organic feeding, the breeds of pig that are most suitable for organic farming, up to date information on the nutritional requirements of pigs, and examples of diets formulated to organic standards.